Designing Interactive Systems Conference 2021 2021
DOI: 10.1145/3461778.3462042
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Personalized Vibrotactile and Thermal Patterns for Affect Regulation

Abstract: The growing HCI interest in wellbeing has led to the emerging area of haptics for affect regulation. In such technologies, distinct haptic patterns are usually designed by researchers; however, current work provides a limited reflection on the rationale for the implemented patterns or the choice of haptic modality. We also know little about how people may benefit from engagement in designing such patterns and what design principles underpin them. We explored vibrotactile and thermal modalities to address these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 86 publications
1
14
0
Order By: Relevance
“…HCI researchers (e.g., [78,85,86]) have used temperature as a signal to understand elicited emotions and communicate information. There are several studies by Wilson et al [85,86] exploring the relationship between temperature and elicited emotions.…”
Section: Thermal Feedback In Hcimentioning
confidence: 99%
See 1 more Smart Citation
“…HCI researchers (e.g., [78,85,86]) have used temperature as a signal to understand elicited emotions and communicate information. There are several studies by Wilson et al [85,86] exploring the relationship between temperature and elicited emotions.…”
Section: Thermal Feedback In Hcimentioning
confidence: 99%
“…They found a distribution of arousal and valence values assigned to various temperature inputs [86] and reported that most participants related warmth to presence and high quality of content while cold meant absence and poor quality of content [85]. A recent study by Umair and colleagues [78] asked participants to choose a thermal signal to receive when they were stressed, and half the participants chose cold while the other half chose warm. Umair recommends that individual personalization is crucial to making temperature signals understandable.…”
Section: Thermal Feedback In Hcimentioning
confidence: 99%
“…Affective Sleeve [57] is a sleeve that provides heat and tension created by shape-memory alloy to forearm. Umair et al [75] explored the personalized vibrotactile and thermal patterns for affect regulation, which provides an option of utilizing the vibrotactile pattern to be personalized to regulate not only the heart rate but also the breathing rate. Their work focused on evaluating the effect of personalized intervention patterns, frequency, and intensity for affect regulation using commercial products rather than exploring a new haptic technology.…”
Section: Breathing Guidance During Daily Activitiesmentioning
confidence: 99%
“…Conversely, there has been a growth in research activity investigating the potential of tangible interaction for supporting well-being. Examples include material exploration with shape-changing, haptics and e-textiles technologies to support bodily awareness [1,14,18], wearable artifacts for remote engagement [4], mindfulness [9,10], and affect regulation [19,20]. Practitioners who are exploring embodied interaction and somaesthetic design have argued for the importance of contact and sensory interaction for well-being [2,7,12].…”
Section: Introductionmentioning
confidence: 99%